Impact of non-thermal plasma on the abatement of Perfluorinated compounds present in minute quantities in water effluents - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Fedorova, Nataliia; Poser, Alexander; Swoboda, Peter; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Based on the strongest C-F bonds backbone, Perfluorinated compounds (PFCs) are manmade chemicals that are omnipresent due to their immense use for the production of various products. Currently, these are also addressed as global contaminants, and are present on the word market since middle of the 20 th century. Non biodegradability and high half-life times generate serious adverse effects on humans and wild life. This calls for remediation. Updated lifetime health advisory, and water quality standards have been issued for PFCs by different US and European environmental agencies, but the conventional techniques for remediation are either inefficient, or turn out to be uneconomic, especially dealing with extremely minute quantities present in effluents. The present study copes with the reduction/removal of low concentrated (<1 μg/l) PFCs from waste water, using non-thermal atmospheric plasma (NTAP). The research experimentally investigates influences of different parameters e.g. plasma gases (air, O2 and N2), treatment times (up to 10 min.) and nozzle/reactor sizes on the reduction of PFC concentrations. Promising results were obtained with NTAP exposure on the PFC concentration levels. In less than 200 seconds, the concentration thresholds of below 50% of initial PFCs concentration was reached in most of the tests within the shown experimental setup. The final concentration of PFCs was strongly dependent on the tested parameters. The decreasing pH value of the water was found to be a limiting factor for the lower PFCs concentration threshol
Keywords: Non-thermal atmospheric plasma; PFC removal; waste water treatment